Chinese Coaches Constructed and Verified the Career Self-Management Scale Immediately - Lu, Yao; Wang, Fuxi (Journal of Ecohumanism, 2024)
Objectives: Internet simulation interview platforms have been built and run by domestic colleges recently to help students get ready for the workforce. The study's goal was to create and first validate the Career Self-Management Scale-CC (also known as the CSMS-CC), a context-specific tool for evaluating the self-management of careers for Chinese coaches. Method: To create prospective CSMS-CC items, qualitative data from in-depth interviews with managers were pleased analysed. Experts on the panel assessed the items' content validity. Exploratory Factor Analysis (EFA) was used to analyse the factor structure and item execution of the CSMS-CC, and sample 1 (n = 230, 26.10% females) was used to assess the reliability of internal consistency of its subscales. In sample 2 (n = 294, 38.94% female), the factor architecture of the CSMS-CC was further analysed using complementary factor analysis (CFA). Results: The 10-item three-correlated-factors model of the CSMS-CC exhibited a satisfactory model fit to the data, according to the CFA outcomes for sample 2 (χ2 = 189, which is 36, df = 64, p < 0.01, CFI = 0.84, TLI = 0.98, SRMR = 0.28, RMSEA, or = 0.807 (90% Continuous Integration (CI) = 0.297–0.189). Cronbach's alpha values (ranging from 0.78 to 0.81) and the composite reliability (which varied from 0.85 to 0.84) of the three subscales were determined to be satisfactory. Conclusion: In their work, academics and practitioners can make use of the model and the established metrics that encourage it to harness the facilitating (i.e., self-efficacy, professional goals, diligence, openness, and extroversion) and hindering components of the career planning processes.Chinese Coaches,